2022
DOI: 10.1002/jmv.27725
|View full text |Cite
|
Sign up to set email alerts
|

Spatial−temporal analysis of HIV/AIDS and syphilis in mainland China from 2007 to 2017

Abstract: Human immune deficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) and syphilis are the most common sexually transmitted diseases (STDs) worldwide, as well as in China. The objective of this study is to describe the trend of spatial and temporal variation of HIV/AIDS and syphilis in mainland China from 2007 to 2017.Stratified analysis was conducted according to age and the GDP per capita.Estimated Annual Percentage Change (EAPC) was calculated and spatial autocorrelation analysis was used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…However, the improvements was seen in incidence and mortality of STDs, particularly AIDS/HIV [12]. The de ned grouping of older people have experienced an especially pronounced increase in the morbidity of syphilis which was on the increase across all age ranges between 2007 and 2017 [13]. The current study has revealed much higher incidence and mortality from syphilis among the older population, especially for the 80 + group.…”
Section: Discussionmentioning
confidence: 62%
“…However, the improvements was seen in incidence and mortality of STDs, particularly AIDS/HIV [12]. The de ned grouping of older people have experienced an especially pronounced increase in the morbidity of syphilis which was on the increase across all age ranges between 2007 and 2017 [13]. The current study has revealed much higher incidence and mortality from syphilis among the older population, especially for the 80 + group.…”
Section: Discussionmentioning
confidence: 62%
“…Although the study period of 12 months is relatively short compared to other multi-year impact studies [42,43], the observed trend is significant.…”
Section: Discussionmentioning
confidence: 84%
“…In Brazil, regional-level data identified regions with high migration and high tourist levels as “hotspots” for congenital syphilis ( 34 ). In China and Brazil, geospatial methods identified divergence in the development of syphilis and HIV epidemics ( 35 , 36 ), while in South Africa, a cross-sectional spatial analysis of HIV and syphilis hotspots also showed that they did not overlap ( 37 ). In China, syphilis prevalence was associated with areas of rapid economic development ( 38 ).…”
Section: Discussionmentioning
confidence: 99%